Intergenerational Continuity in Child Maltreatment: Explicating Underlying Mechanisms - Martoccio, Tiffany L. (Journal of interpersonal violence, 2022)
The current study examined direct and indirect effects of a mother’s history of childhood physical and sexual abuse on her child’s officially reported victimization. This prospective, longitudinal study followed a community-based sample of 499 mothers and their children. Mothers (35% White/non-Latina, 34% Black/non-Latina, 23% Latina, and 7% other) were recruited and interviewed during pregnancy, and child protective services records were reviewed for the presence of the participants’ target child between birth and age 3.5. Whereas both types of maternal maltreatment history doubled the child’s risk of child protective services investigation, mothers’ sexual abuse history conferred significantly greater risk. Pathways to child victimization varied by type of maternal maltreatment history. Mothers who had been physically abused later demonstrated interpersonal aggressive response biases, which mediated the path to child victimization. In contrast, the association between maternal history of sexual abuse and child victimization was mediated by mothers’ substance use problems. Study implications center on targeting child maltreatment prevention efforts according to the mother’s history and current problems.